Momongu Kambungu Program Through White Copra Processing in Totopo Village, Gorontalo Regency - Yusuf, Taufiq Ismail; Tansa, Salmawaty; Tolago, Ade Irawaty (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Community Service Activities are an effort by Gorontalo State University so that the Tridharma of Higher Education can be implemented by raising the main theme